2012
DOI: 10.1016/j.jgeb.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular comparative analysis of component 1 (DNA-R) of an Egyptian isolate of banana bunchy top nanovirus isolated from banana aphid (Pentalonia nigronervosa)

Abstract: We are reporting a molecular comparative analysis of component 1 BBTV-DNA-R of an Egyptian isolate of (BBTV) and 30 different geographical isolates. DNA was extracted from BBTVinfected adult banana aphids collected from El-Qalubia Governorate, Egypt. Using specific primers the BBTV-DNA-R was amplified, cloned into a prokaryote vector, sequenced and a molecular comparative analysis of BBTV-DNA-R of this study and some overseas isolates of BBTV-infected banana plants was determined. Results showed that the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These results were corroborated by the distribution of the isolates in the phylogenetic tree based on nucleotide sequences, which showed a clear subdivision of the isolates into two distinct clades, with all the Mozambican isolates grouped together with the isolates of the PIO group. Other authors studying isolates from different African countries also reported that the isolates belonged to the PIO group [21,37,38,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…These results were corroborated by the distribution of the isolates in the phylogenetic tree based on nucleotide sequences, which showed a clear subdivision of the isolates into two distinct clades, with all the Mozambican isolates grouped together with the isolates of the PIO group. Other authors studying isolates from different African countries also reported that the isolates belonged to the PIO group [21,37,38,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The genome of BBTV is multipartite, comprising of six circular components (Figure 2) with an approximate size of 1.1 kb each (Burns, Harding, & Dale, 1995; Harding, Burns, & Dale, 1991; Harding, Burns, Hafner, Dietzgen, & Dale, 1993) and are known to promote the pathogenicity of the virus. They were initially named as DNA 1–6 but recently named as DNA‐R, DNA‐U3, DNA‐S, DNA‐M, DNA‐C, and DNA‐N, respectively (Abdel‐Salam, Dahot, & Sadik, 2012; Harding et al., 1991; Wu, You, & Soong, 1994). The six components are encapsidated within separate virions, each about 18–20 nm in diameter (Harding et al., 1993).…”
Section: Banana Bunchy Top Virusmentioning
confidence: 99%
“…DNA‐R encodes a replication initiation protein (Rep) responsible for initiating viral DNA replication, DNA‐S encodes the coat protein (CP), DNA‐C encodes the cell‐cycle link protein (Clink), DNA‐M encodes the movement protein (MP), and DNA‐N encodes the nuclear shuttle protein (NSP), while the function of DNA‐U3 is unknown (Abdel‐Salam et al., 2012; Burns et al., 1995; Wanitchakorn, Hafner, Harding, & Dale, 2000; Wanitchakorn, Harding, & Dale, 1997). BBTV DNA‐R, DNA‐U3, DNA‐S, DNA‐M, DNA‐C, and DNA‐N (DNA‐1–DNA‐6) have been consistently associated with BBTV isolates globally, suggesting they are integral components of the BBTV genome.…”
Section: Banana Bunchy Top Virusmentioning
confidence: 99%
“…It is an icosahedral virus consisting of six circular single-stranded DNA genome components i.e., DNA-R, DNA-U3, DNA-S, DNA-M, DNA-C and DNA-N (previously named DNA-1 to DNA-6, respectively) (Elayabalan et al 2015). The sequences length of each genome component is approximately 1 to 1.1 Kb, and the transcripts have been mapped (Abdel-Salam et al 2012). DNA-R encodes a master replication-associated protein (rep), DNA-S a capsid protein (cp), DNA-M a movement protein (mp), DNA-C a cell-cycle link protein (Clink), and DNA-N a nuclear shuttle protein (nsp) gene.…”
mentioning
confidence: 99%